Estimating option prices using log-gamma model. - Tan, Catherine Khee Chang. (2008)
Following the major breakthrough by Fisher Black, Myron Scholes and Robert Merton with the development of the Black-Scholes model, pricing and hedging of options have since been largely influenced by this model. In this paper, we study the pricing errors of options using the log-gamma process and a comparison analysis will be performed against the Black-Scholes model.